Self-directed learning in higher education environment : do pre-university education and learning styles play a role? - Maung, Mala; Azman, Abdullah; Zoraini Wati, Abas
The majority of students undergoing the medical programme at the International Medical University (IMU) transfer to partner medical schools worldwide after the phase 1 programme. Thus it is desirable to inculcate self-directed learning (SDL) skills to enable them to adapt to the varied learning strategies of these schools. As learner characteristics importantly influence successful SDL, the effect of learning styles and pre-university education on the appreciation of SDL in relation to the learning resources was assessed in 708 students undergoing IMU’s medical curriculum. Male students rated appreciation of SDL significantly higher than females. The ratings were consistently higher for SDL as a good learning method compared to the utilisation of resources for all the semesters with a positive correlation. The majority of students entering IMU have experienced STPM, (Malaysian equivalent of matriculation), South Australian matriculation (SAM) and GCE-A level. Although difference in responses is seen among the various pre-university education groups, this is not significant. Generally, there are more reflective than active, sensing than intuitive, visual than verbal and sequential than global learners. Appreciation of SDL and utilisation of IMU resources are positive irrespective of learning style. These findings indicate that the majority of students, irrespective of learning style and pre-university education appreciate the need to develop SDL. The study identified “receiving”, “adaptation” and “acceptance” phases in students as they progress and adapt through a higher education environment. Importantly, providers of higher education must be aware of these phases and address them accordingly. (Authors' abstract)